Age- and sex-related differences in force-velocity characteristics of upper and lower limbs of competitive adolescent swimmers - Nikolaidis, P. T. (Journal of Human Kinetics, 2012)
While there is a direct relationship between maximal anaerobic power (Pmax) and swimming performance, the relationship between upper and lower limbs with regard to Pmax and force-velocity (F-v) characteristics is not clear. The aim of the present study was to examine the effect of age and sex on the ratios of mechanical characteristics between upper and lower extremities of adolescent swimmers. Seventeen girls (aged 14.7±1.8 yr) (mean±standard deviation) and 28 boys (14.6±1.4 yr), all members of competitive swimming clubs, performed a F-v test for both legs and arms. In legs, boys had higher values of Pmax (t43=2.4, p43=3.4, p0 (t43=4.3, p0 (t43=1.0, p=0.31) and v0/F0 (t43=0.55, p=0.59). In arms, boys had higher values of Pmax (t43=3.2, p43=3.9, p0 (t43=3.4, p0 (t43=1.9, p=0.06) and v0/F0 (t43=0.16, p=0.87). However, no sex difference was found with regard to the ratios of Pmax (t43=1.9, p=0.06), F0 (t43=1.2, p=0.23) and v0 (t43=1.3, p=0.20) between upper and lower extremities. There was direct relationship between age and Pmax of legs (r=0.64, p